Design and manufacturing of the combined quadrupole and corrector magnets for the LIPAc accelerator high energy beam transport line. (1st August 2022) - Brañas, B.; Castellanos, J.; Oliver, C.; Campmany, J.; Fernández, F.; García, M.; Kirpitchev, I.; Marcos, J.; Massana, V.; Méndez, P.; Mosca, J.; Toral, F.; et al.
Abstract: The International Fusion Materials Irradiation Facility (IFMIF) is a project aiming to investigate candidate materials to be used in the most exposed zones of future fusion reactors. The linear IFMIF prototype accelerator (LIPAc), presently under commissioning in Rokkasho, Japan, is a prototype of the frontend section of one of the IFMIF accelerators. Eight quadrupole magnets, six pairs of corrector magnets and one dipole are responsible for generating the magnetic fields needed for a proper beam handling along the 10 m long LIPAc high energy beam transport line, which connects the end of the superconducting radio frequency Linac with the beam dump. A novel design of combined magnets with the correctors integrated in the quadrupole poles is chosen for compactness reasons. The different stages of the production of the combined magnets, from the magnetic and mechanical design to their manufacturing and testing, including exhaustive characterization of the magnetic performance are described in this work. The results from the tests revealed the quality of the magnetic field produced. The materials selection was done carefully, to withstand the high levels of ionizing radiation expected at the magnet locations. This paper focuses on the activities performed in Europe, before sending the magnets to Japan for their installation and commissioning at the Rokkasho site.